Learn to balance your life - Michael (London, 2004)
This title equips the reader with everything needed to find fulfulment in all areas of life - identify priorities and allow enough time for them; maximise finances; use work and leisure time enjoyably and profitably; and make the home a calming yet energising place to live.
Keywords: Life